PENGARUH ASIMETRI INFORMASI, LEVERAGE, DAN KOMPENSASI BONUS TERHADAP EARNING MANAGEMENT PADA PERUSAHAAN GO PUBLIC - Kotim, Kotim; Wahidahwati, Wahidahwati; Fadjrih, Nur (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2023)
The study aims to examine 1) The effect of Information asymmetry on earning management, 2) The Effect of bonus compensation on earning management, 3) The leverage effects on earning management of the manufacturing companies that were anlisted in BEI. The independent variables applied are information asymmetry, leverage and bonus. The methodology used multiple linear regression analysis and purposive sampling which comprising the whole number of 162 sample in 2008-2016. The research findings indicated that between the listed variables, information asymmetry and leverage hold positive impacts on profit management of long term discreationary accrual, but did not hold any on short term discretionary accrual. Meanwhile bonus hold positive impacts on profits management of short term discretionary accrual but did not hold any on long term discretionary accrual.